Prevalent and incident anaemia in PARADIGM-HF and effect of sacubitril/valsartan. (3rd October 2022) - Curtain, J; Adamson, C; Jhund, P S; Desai, A S; Lefkowitz, M P; Rizkala, A R; Rouleau, J L; Swedberg, K; Zile, M R; Solomon, S D; Packer, M; McMurray, J J V
Abstract: Background: Anaemia is common in patients with HFrEF and is associated with poor clinical outcomes. Although they reduce rates of mortality and heart failure hospitalization, renin-angiotensin (RAS) blockers lower haemoglobin and may induce anaemia. Concomitant neprilysin inhibition might ameliorate this effect of RAS blockers. Purpose: We investigated the effect of sacubitril/valsartan compared with enalapril on clinical outcomes, according to anaemia status, and on haemoglobin levels in PARADIGM-HF. Methods: Patient characteristics and clinical outcomes were compared between patients with and without anaemia (defined as haemoglobin <120 g/L in women and <130 g/L in men) at baseline. We investigated the effect of randomized treatment (sacubitril/valsartan or enalapril) on clinical outcomes according to anaemia status at screening. We also examined the effect of treatment on change in haemoglobin from baseline and on the incidence of anaemia. The primary endpoint in PARADIGM-HF was the composite of heart failure hospitalization or cardiovascular death. Results: Of 8239 participants with a baseline haemoglobin measurement, 1677 (20.4%) were anaemic. Compared to those without anaemia, patients with anaemia had a more severe heart failure profile, worse kidney function, greater neurohormonal derangement and worse clinical outcomes. Sacubitril/valsartan, compared to enalapril, reduced the risk of the primary endpoint similarly in patients with anaemia (HR 0.84, 95% CI 0.71–1.00) and without anaemia (HR 0.78, 95% CI 0.71–0.87), p-value for interaction=0.478. Between baseline and 12 months, haemoglobin decreased by 1.5 (95% CI 1.7 to 1.2) g/L with sacubitril/valsartan compared with 2.3 (2.6 to 2.0) g/L with enalapril group: mean difference 0.8 (95% CI 0.5 to 1.2) g/L, p<0.001. The between-treatment difference apparent by 12 months, persisted up to 36 months. Patients assigned to sacubitril/valsartan were less likely to develop new anaemia at 12 months [321 of 2806 (11.4%)] compared to patients randomized to enalapril [440 of 2384 (15.6%)], odds ratio 0.70 (95% CI 0.60–0.81), p<0.001. Conclusions: Compared to enalapril, sacubitril/valsartan reduced mortality and hospitalization in HFrEF patients with and without anaemia. Haemoglobin decreased less with sacubitril/valsartan and the incidence of new anaemia was lower in the sacubitril/valsartan group compared with the enalapril group. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): PARADIGM-HF was funded by Novartis.